การวิเคราะห์ความคล้ายของการไหลแบบราบเรียบของเจ็ต ที่หมุนควงในกระแสลมตามที่ไม่หมุนควง - สุเมธ ไตรภพสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Effects of swirl and coflow on the characteristics of swirling jet in nonswirling coflow were investigated. Similarity anslysis with similarity transformations u = um f(eta)+u1 and w = wm g(eta) was used in order to transform the system of governing partial differential equations (PDE) into the system of ordinary differential equations (ODE). The system of ODE was then solved numerically for velocity and pressure profiles, and for growth and velocity decay rates. The analysis was performed for 3 cases according to the assumption regardng swirl 1) no swirl, 2) weak swirl, and 3) any swirl, as specified by the ratio between the tangential velocity and the axial velocity (Sr = wm/um). Each case is further analyzed for another 3 subcases according to the assumption regarding coflow: 1) no coflow (u1 = 0), 2) strong coflow (u1>>um), and 3) any coflow, as specified by the ratio between the coflow velocity and the jet excess velocity (Vr = u1/um). The results for nonswirling jet showed that the axial velocity profile was similar to Gaussian curve, which became narrower as Vr increased. This was due to the relative increase of the convection of x-momentum along the axial direction as opposed to that along the radial direction as Vr increased. From another viewpoint, the velocity difference between the jet and the coflow induced shear layer. As a result, when the coflow velocity increased, the velocity difference decreased, causing a reduction in strength of the shear layer and, consequently, the thickness of the jet. The results for weak swirling jet showed that the axial velocity profile was similar to that of nonswirling jet and the tangential velocity profile was Rankine-vortex-like. In addition, the tangential velocity profile became narrower as the coflow velocity increased. Furthermore, the dimensionless pressure difference ((p(infinity)-p)/pw(2)(m)) on the jet axis was found to be a positive constant. Since the tangential velocity wm decreased as x(-2), (p(infinity)-p) decreased at the same rate. This implied that the pressure along the jet axis increased in the downstream direction, creating an adverse pressure gradient along the jet axis. In the analysis for general swirling jet, two integral constraints: linear momentum and angular momentum constraints, were alternately used. In case of no coflow with linear integral momentum constraint, the axial velocity profile was similar to Gaussian curve, which became wider as Sr increased. At high Sr, the position of the maximum axial velocity deviated from the jet axis, resulting in a wake component at the center. In addition, the tangential velocity profile was similar to Rankine-vortex, which became narrower as Sr increased. In other words, increasing of Sr intensified the vortex core. When the angular momentum constraint was used, the solution differed from that of the linear momentum constraint. In the case of general coflow (Vr), the results for linear momentum constraint indicated that, as Sr increased, the growth rate of the jet increased. On the contrary, as Vr increased, the growth rate of the jet decreased. In other words, swirl and coflow had counter effect. Furthermore, at low Sr, as Vr increased, the coflow became more influential on the growth rate of the jet than the swirl. As a result, the characteristics of the jet became similar to nonswirling jet. When the angular momentum constraint was used in this case, the solution differed from that of the linear momentum constraint.